A theoretical reflection on trust in interpersonal relations in organizational environments (Research, Society and Development, 2021)
Appreciating trust from the point of view of mutual influence between the parties that sometimes face conflicts of interest, understanding how this feeling is configured in relationships, understanding the reciprocity and the impact of this on the organizational environment, is the point of reflection of this article. The purpose was to develop a theoretical reflection on the effects of trust and its elements in business environments, marked by cultures and relationships that present many particularities. From already consolidated references, arguments, concepts and theories that brought analytical substances were rescued. The theoretical discussion culminated in the disseminated approaches and concepts of trust, with the presentation of studies that approached trust from various perspectives. Some constituent elements of trust have been discriminated against, which, isolated or combined with each other, have an effect on the decision of one person to trust or not to trust another.